Implementasi Sistem Manajemen Keuangan pada Lembaga Khalifah Cendekia Mandiri Moncongloe Maros - Rahmah, Rahmah; Damopolii, Muljono; Hasan, Mardhiah; Jamil, Muhammad (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
This research aims to determine the financial management system applied to financial management at the Khalifah Cendekia Mandiri educational foundation. This foundation has overseen three formal and non-formal educational institutions, namely the Integrated Islamic Kindergarten and Integrated Islamic School and the Al Qur'an Education Park. There were four subjects in this research, namely the chairman of the foundation, the principal, administrative staff/treasurer and also teachers. This research uses primary and secondary data as data sources. Meanwhile, the tools used in collecting data are observation, interviews and documentation. Based on the research results, the Khalifah Cendekia Mandiri educational institution has implemented discipline in the financial management system, namely it has gone through a maximum planning and regulation process as well as transparent management.